A Longitudinal Evaluation of Data-Based Planning (PBD) ffectiveness in Improving Numeracy Skills - Dwi Rismi, Ocy; Riyadi , Riyadi; Soeprijanto , Soeprijanto; Badrujaman, Aip (Jurnal Evaluasi Pendidikan, 2025)
Trends in numeracy skills across different content areas and cognitive levels continue to pose a considerable challenge in integrated Islamic elementary schools, affecting students' overall academic achievement. This longitudinal study assesses the effectiveness of Data-Based Planning (Perencanaan Berbasis Data/PBD) in bridging these gaps and improving numeracy skills among students at SDIT Al-Khoiriyah Al Husna during the period from 2023 to 2025. The study utilizes a mixed-methods explanatory sequential design, combining quantitative growth and gap analyses of students’ numeracy achievement across various content domains (Number, Algebra, Geometry) and cognitive levels (Knowing, Applying, Reasoning) with qualitative document analysis of PBD implementation cycles. Results indicate significant enhancements in basic numeracy skills, especially in minimal competency and the Number domain, during the initial stage of PBD implementation. However, enduring disparities exist among cognitive levels, especially in higher-order reasoning skills, which demonstrated slower advancement despite focused interventions. This underscores the persistent difficulty of properly cultivating higher-order thinking in numeracy skills. The research highlights the essential importance of teacher competence and adaptable, data-driven techniques in maintaining significant development. These findings provide significant implications for enhancing educational quality assurance processes in integrated Islamic elementary schools.